2020
DOI: 10.2196/preprints.24196
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parents’ Attitudes Toward School Students’ Overuse of Smartphones and Its Detrimental Health Impacts: Qualitative Study (Preprint)

Abstract: BACKGROUND Parents’ awareness of the risk of the overuse of smartphones (SPs) among their children and parents’ attitudes towards this societal phenomenon are crucial factors to consider when investigating the causes and effects of, and interventions to control, this public health issue. OBJECTIVE The aim of this study is to explore the awareness and attitudes of parents regarding SP overuse am… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…While unable to find any studies that cite a parenting knowledge gap in this area, we believe the latter may be explained by the especially close bonding mothers have with young children, which would lead them to be more concerned about smartphone exposure among their offspring. This view is supported by Buabbas et al, 23 who reported that mothers supervised their children's smartphone use more than fathers.…”
Section: Discussionmentioning
confidence: 79%
“…While unable to find any studies that cite a parenting knowledge gap in this area, we believe the latter may be explained by the especially close bonding mothers have with young children, which would lead them to be more concerned about smartphone exposure among their offspring. This view is supported by Buabbas et al, 23 who reported that mothers supervised their children's smartphone use more than fathers.…”
Section: Discussionmentioning
confidence: 79%
“…Research on smartphone overuse has focused on youth (e.g., Buabbas et al, 2021;Kim et al, 2020), and emerging adults (see review from Busch & McCarthy, 2021), with little research focusing on individuals in the established adulthood stage of life (Mehta et al, 2020). This study explored smartphone use by established adults who perceive that they overuse their smartphones and/or social media.…”
Section: Purpose Of the Current Studymentioning
confidence: 99%
“…The improper use of smartphone can cause problems such as smartphone addiction, which is categorized as behavioral addictions. This phenomenon can affect many aspects of the lives of adolescents and youth, including education and physical health, and may be associated with problems such as interpersonal problems, anger, aggression, and excitement [6]. Among the main consequences of smartphone addiction are negative psychological effects, psychosomatic, and physical disorders such as; digital eye strain, itchy eyes, headache caused by eye fatigue, and text neck.…”
Section: Introductionmentioning
confidence: 99%